2004
DOI: 10.1557/proc-849-kk8.4
|View full text |Cite
|
Sign up to set email alerts
|

Physical Self-Assembly And Nano-Patterning

Abstract: It is known that oblique angle deposition (or glancing angle deposition) can create 3D architectures that are otherwise difficult to produce using the conventional lithographic techniques. The technique relies on a self-assembly mechanism originated from a physical shadowing effect during deposition. In this paper we show examples of 3D nanostructures obtained by this oblique angle deposition on a templated substrate with regularly spaced pillar seeds. We show that common to this technique is the phenomenon of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…3 and its inset, that the difference between mound radii in x-and y-axis increases as does the coverage or the deposition angle. This prediction agrees well with the experimental results of Dijken et al 7 and Lu et al 14 , where such side way growth of the mound with high aspect ratio has been observed with the deposition at grazing angle. In regards to Fig.…”
Section: B Mound Radiussupporting
confidence: 92%
See 1 more Smart Citation
“…3 and its inset, that the difference between mound radii in x-and y-axis increases as does the coverage or the deposition angle. This prediction agrees well with the experimental results of Dijken et al 7 and Lu et al 14 , where such side way growth of the mound with high aspect ratio has been observed with the deposition at grazing angle. In regards to Fig.…”
Section: B Mound Radiussupporting
confidence: 92%
“…9 (c)-(e)) which strikingly differs from what has been observed in the experiments. 7,14 This is understood by the fact that the flux blocked by the screening effect on the SH-side results in the increase of the flux on the IL-side (Fig. 10), which looks as if the blocked flux is simply displaced to the IL side.…”
Section: B the Steering Effects Vs The Screening Effectsmentioning
confidence: 98%
“…Thus, if we use a prepatterned substrate, as is often the case in the selective growth of the columns using low temperature glancing angle deposition, (14,15) we can achieve a patterned growth of nanowhiskers.…”
Section: Selective Growth Of Nanowhiskers By Shadowing Effectmentioning
confidence: 99%
“…Thus, if we use a prepatterned substrate, as is often the case in the selective growth of the columns using low-temperature GLAD (14,15), we can achieve patterned growth of nanowhiskers.…”
Section: Selective Growth Of Nanowhiskers By Shadowing Effectmentioning
confidence: 99%